SOLUTIONS FOR AGRICULTURAL DEVELOPMENT WITH HIGH-TECH APPLICATIONS IN QUANG TRI PROVINCE TO 2030 - Xuan Phuong, Hoang; Ba Long, Nguyen; Thi Thu Thao, Xuan; Van Thung, Nguyen (Journal of Forestry Science and Technology, 2019)
Despite certain success been made recently, traditional agricultural production in Quang Tri province still encounters a lot of difficulties and limitations, need to apply technical advances, especially in high-technology to overcome these limitations. There have been initially successful models of applying high technology in agricultural production such as model of growing vegetables and fruit trees in net house; using advanced varieties, watering economically; Intensive shrimp farming model using probiotics; model of rice cultivation using fertilizers and biological plant protection drugs. The study identifies that some local animals and crops have advantages in high-tech application such as rice, coffee pepper, fruit trees, pig, cow, poultry, and aquaculture. To develop hi-tech agriculture in Quang Tri province, there should be synchronized solutions, in which important solutions are planning high-tech agricultural production zones - areas and identifying suitable technologies for each specific plant and particular zone. The study identified that by 2030 Quang Tri province will build 2 areas of high-tech agriculture and 33 areas of high-tech agriculture. At the same time, other solutions should be also conducted such as promulgating policies that support the development of high-tech agriculture; solutions for land, training human resources, forming models, creating linkages, organizing production and promoting propaganda about high-tech agriculture.